천식 악화로 응급실을 방문한 소아 환자의 표준 진료 지침 적용 효과 - 이진영; Jin Young Lee; 남지선; Ji Sun Nam; 전윤홍; Yoon Hong Chun; 윤종서; Jong Seo Yoon; 김현희; Hyun Hee Kim; 김진택; Jin Tack Kim; et al. (Chʻŏnsik mit alrerugi, 2011)
Background: The use of the clinical pathway (CP) for asthma management may ensure appropriate treatment for asthmatic patients. Objective: The objective was to evaluate the effect of the CP on the management of asthma exacerbation in the emergency department (ED) of a hospital in South, Korea. Method: The subjects consisted of the patients being children at the ages of 3∼15 years presented with asthma exacerbation in the ED. We conducted a retrospective before-after study on the CP under the 2006 GINA guidelines. The CP was implemented in 2008 (postimplementation), whereas the strategy used in 2007 (pre-implementation) was not standardized. Result: In 2008, 3 of the 36 patients were hospitalized (8.3%, post-implementation); in 2007, 7 of 53 patients were hospitalized (13.2%, pre-implementation) (P=0.734). According to the results of outpatient observation, continuous wheezing decreased from 12 of 21 patients (57.1%) in 2007 to 7 of 22 patients (31.8%) in 2008 (P=0.043), and the administration of relievers decreased from 9 of 21 patients (42.9%) in 2007 to 4 of 22 patients (18.2%) in 2008 (P=0.038). Conclusion: The CP was successfully implemented in the ED of a hospital in South, Korea and reduced wheezing and the need for relievers in the outpatient clinic. (Korean JAsthma Allergy Clin Immunol 2011;31:41-47)